Evaluation of Learned Resourcefulness and Marital Adjustment in Individuals With and Without Disabilities. - Ünal, Esra; Ağralı, Cansu (American Journal of Family Therapy, 2026)
This study aimed to evaluate learned resourcefulness and marital adjustment in visually impaired and non–visually impaired married individuals. A total of 112 participants took part in the study. Findings revealed a positive correlation between learned resourcefulness and marital adjustment, with visually impaired individuals scoring significantly higher than their non–visually impaired counterparts. Based on these results, it is recommended that family therapists and health professionals integrate learned resourcefulness-based strategies to support visually impaired individuals in overcoming relationship challenges.